THE EFFECTIVENESS OF TEACHING SPEAKING BY USING WHATSAPPS OF TENTH GRADE STUDENTS AT MAN 4 KEDIRI - Sari, Estika (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2019)
The aim of the research was to analyze whether Whatshapp Messenger (WA) was effective to be used in teaching speaking descriptive at the tenth grade of MAN 4 Kediri. This research was quantitative research approach, whereas the research design used was posttest-only control-design. This research used two classes which became experimental group (MIA 3) and control group (MIA 4). In experimental group was taught by using Whatshapp Messenger, whereas control group was taught without Whatshapp Messenger. The instruments used in the research was written test. The procedure lasted 3 meetings and 1 meeting to do test. The result of t-test showed that: the mean score of experimental group (M = 81.15) was higher than control group (M = 70.29), and independent-samples t-test which values of the sig. 2-tailed was 0% or 0.000 and 0.000 < 0,05. Thus, it could be concluded that Whatshapp Messenger was effective in teaching and learning of English speaking descriptive text. This result suggests that the speaking aspects which the students significantly outperformed were (1) Pronunciation (2) Vocabulary (3) Grammatical (4) Fluency (5) Comprehension and (6) Expression.